2019
DOI: 10.7150/ijbs.31484
|View full text |Cite
|
Sign up to set email alerts
|

ASB6 Promotes the Stemness Properties and Sustains Metastatic Potential of Oral Squamous Cell Carcinoma Cells by Attenuating ER Stress

Abstract: Up-regulation of ASB6 has been previously associated with late-stage and poor prognosis of oral squamous cell carcinoma (OSCC) patients. To explore the cellular and molecular basis of how ASB6 enhances the malignancy of OSCC, we employed the clonogenicity and migration assays, murine pulmonary metastasis model, Western blot, and immunofluorescence microscopy to characterize the phenotypes of OSCC cells with lentiviral-based stable overexpression or knockdown of ASB6. We found that ASB6 overexpression increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The up-regulation of ASB6 is associated with the elevation of intracellular ROS in oral cancer cells ( Hung et al, 2009 ). A recent study also showed that overexpression of ASB6 can decrease intracellular ROS and endoplasmic reticulum stress in the deprived media-induced stress of oral cancer cells ( Hung et al, 2019 ). Therefore, the reduction of intracellular ROS in the LPS-stimulated cells ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The up-regulation of ASB6 is associated with the elevation of intracellular ROS in oral cancer cells ( Hung et al, 2009 ). A recent study also showed that overexpression of ASB6 can decrease intracellular ROS and endoplasmic reticulum stress in the deprived media-induced stress of oral cancer cells ( Hung et al, 2019 ). Therefore, the reduction of intracellular ROS in the LPS-stimulated cells ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Later, ASB6 was found upregulated in oral squamous cell carcinoma, which is a possible consequence of exposure to Areca nut extracts and is co-related with poor survival ( Hung et al, 2009 ). Another recent following study from the same group suggested that accumulation of ASB6 may impede ER stress and cause gain of stemness and metastasis feature of oral squamous cell carcinoma, although the underlying molecular mechanism remains elusive ( Hung et al, 2019 ). Therefore, the detailed molecular function of ASB6, especially in pathological conditions, is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…During monocyte differentiation by macrophage colony stimulating factor (M-CSF), the ER undergoes structural as well as functional reorganization to perform the new cell functions, leading to ER stress and upregulated UPR [31] The UPR is a pro-survival mechanism that is activated and regulates cells by maintaining protein homeostasis via accumulation of unfolded, misfolded, and immature proteins in the ER; however, the UPR can also trigger cell death under unresolved levels of improper protein accumulation [32,33]. Moreover, aberrant activation of endoplasmic reticulum stress (ER stress) has been considered to have a major role in the regulation of tumor growth, invasion, metastasis, and its microenvironment, as well as in response to chemotherapy, targeted therapies, and immunotherapy [34,35]. The alleviation of ER stress prevents the otherwise increasing potential of cells to acquire or sustain stem-cell properties and metastatic capacity, thereby enhancing the malignancy of oral squamous cell carcinoma cells by increasing the population of cancer stem or stem-like cells [36].…”
Section: Discussionmentioning
confidence: 99%